Inferences on glacial flow from till clast dispersal, Waterford area, New Brunswick - Broster, B.; Munn, M.; Pronk, A. (Géographie physique et Quaternaire, 1997)
AbstractDispersal patterns for till clasts from the Waterford area, New Brunswick, are compared to source outcrops and used to confirm dominant ice-flow directions in a region reported to show multiple and conflicting striae directions. The results demonstrate that the last glaciation produced elongated south and eastward trending dispersal patterns, indicative of the dominant ice-flow directions. Clasts have been derived locally. Train lengths generally vary from 4 km to about 10 km for material in basal till, but can achieve distances up to 26 km because of transport in englacial positions. Felsic and intermediate metavolcanic and intrusive clasts occur in till at locations north of outcropping plutons on the Central Plateau. The till overlies part of the Carboniferous Basin and has been derived in part, from underlying conglomerate bedrock. Since these conglomerate units contain fragments from the surrounding areas including the Central Plateau, they provided a secondary source for some lithologies during glaciation. Glacial erosion of underlying conglomerate units may account for occurrences of distinctive till clasts found at other areas of the New Brunswick lowlands, previously thought to imply northward glacial transport.